Effects of Carissa carandas Linn. Fruit, Pulp, Leaf, and Seed on Oxidation, Inflammation, Tyrosinase, Matrix Metalloproteinase, Elastase, and Hyaluronidase Inhibition - Waranya Neimkhum; Songyot Anuchapreeda; Wei-Chao Lin; Shang-Chian Lue; Kuan-Han Lee; Wantida Chaiyana (MDPI AG, 2021)
In this study, the potential of Carissa carandas Linn. as a natural anti-aging, antioxidant, and skin whitening agent was studied. Various parts of C. carandas, including fruit, leaf, seed, and pulp were sequentially extracted by maceration using n-hexane, ethyl acetate, and ethanol, respectively. High-performance liquid chromatography, Folin-Ciocalteu, and Dowd method were used to investigate their chemical compositions. The inhibitory activities of oxidation process, matrix metalloproteinases (MMPs), elastase, hyaluronidase, and tyrosinase were analyzed. Cytotoxicity was determined by 3-(4,5-dimethylthiazol-2-yl)-2,5 diphenyl tetrazolium bromide assay in a human epidermal keratinocyte line (HaCaT). The results exhibited that ethyl acetate could extract the most ursolic acid from C. carandas, while ethanol could extract the most phenolics and flavonoids. The leaf extract had the highest content of ursolic acid, phenolics, and flavonoids. The leaf extracted with ethyl acetate (AL) had the highest ursolic acid content (411.8 mg/g extract) and inhibited MMP-1, NF-kappa B, and tyrosinase activity the most. Ursolic acid has been proposed as a key component in these biological activities. Although several C. carandas extracts are beneficial to human skin, AL has been proposed for use in cosmetics and cosmeceuticals due to its superior anti-wrinkle, anti-inflammation, and whitening properties.